2003
DOI: 10.1021/jf0344744
|View full text |Cite
|
Sign up to set email alerts
|

Andean Yacon Root (Smallanthus sonchifolius Poepp. Endl) Fructooligosaccharides as a Potential Novel Source of Prebiotics

Abstract: The ability of three known probiotic strains (two lactobacilli and one bifidobacterium) to ferment fructooligosaccharides (FOS) from yacon roots (Smallanthus sonchifolius Poepp. Endl) was compared to commercial FOS in this study. Results indicate that Lactobacillus acidophilus NRRL-1910, Lactobacillus plantarum NRRL B-4496, and Bifidobacterium bifidum ATCC 15696 were able to ferment yacon root FOS. FOS consumption apparently depended on the degree of polymerization and the initial FOS composition. L. plantarum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 30 publications
3
81
0
8
Order By: Relevance
“…Yacon also possesses the properties to treat kidney complaints and skin-rejuvenating activity. Fructooligosaccharides are the products recognised and used as food ingredients and prebiotics (Pedreschi et al 2002). Pedreschi et al (2002) found that Lactobacillus plantarum NRRL B-4496 and L. acidophilus NRRL B-1910 completely utilised the GF 2 molecule while Bifidobacterium bifidum was apparently able to utilise molecules with higher DP.…”
Section: Uses Of Yacon Potentials and Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yacon also possesses the properties to treat kidney complaints and skin-rejuvenating activity. Fructooligosaccharides are the products recognised and used as food ingredients and prebiotics (Pedreschi et al 2002). Pedreschi et al (2002) found that Lactobacillus plantarum NRRL B-4496 and L. acidophilus NRRL B-1910 completely utilised the GF 2 molecule while Bifidobacterium bifidum was apparently able to utilise molecules with higher DP.…”
Section: Uses Of Yacon Potentials and Advantagesmentioning
confidence: 99%
“…Fructooligosaccharides are the products recognised and used as food ingredients and prebiotics (Pedreschi et al 2002). Pedreschi et al (2002) found that Lactobacillus plantarum NRRL B-4496 and L. acidophilus NRRL B-1910 completely utilised the GF 2 molecule while Bifidobacterium bifidum was apparently able to utilise molecules with higher DP. Fructooligosaccharides (2 to 9 molecules of fructose) have received much attention as prebiotics due to their small utilisation by the body and their ability to enhance the growth of probiotics.…”
Section: Uses Of Yacon Potentials and Advantagesmentioning
confidence: 99%
“…En la inulina de origen vegetal, las unidades de fructosas enlazados a la glucosa terminal puede variar desde algunas unidades hasta 70, lo que significa que la inulina es una mezcla de oligómeros y polímeros, definiéndose como un polifructano con grado de polimerización (DP) mayor a 30 unidades (Pedreschi et al, 2003;Ricca et al, 2007;Seminario et al, 2003).…”
Section: Sustratos Fuente De Inulinaunclassified
“…Since humans have no enzyme capable of hydrolyzing the β(2→1) bond, these fructans also serve as dietary fiber (Ojansivu et al, 2011). Recently, oligofructans have been classified as prebiotics (Pedreschi et al, 2003). These compounds are transported to the colon and fermented by selected species of gut micro-flora, especially Bifidobacterium and Lactobacillus, both indicators of a balanced gut flora.…”
Section: Introductionmentioning
confidence: 99%